2015
DOI: 10.1371/journal.pone.0141132
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Secondary Structural Element in the Coding Region of the Influenza A Virus Nucleoprotein (NP) mRNA Is Important for the Regulation of Viral Proliferation

Abstract: Influenza A virus is a threat to humans due to seasonal epidemics and infrequent, but dangerous, pandemics that lead to widespread infection and death. Eight segments of RNA constitute the genome of this virus and they encode greater than eight proteins via alternative splicing of coding (+)RNAs generated from the genomic (-)RNA template strand. RNA is essential in its life cycle. A bioinformatics analysis of segment 5, which encodes nucleoprotein, revealed a conserved structural motif in the (+)RNA. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Most previous ASOs for IAV were designed to target mRNA (e.g., AUG region of different segments [ 36–40 ], conserved region [ 41 ], or structures [ 42 ] in NP, or UTRs [ 43 , 44 ]). For IAV vRNA, only the conserved 5′ and 3′ ends forming the panhandle structure have been targeted [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous ASOs for IAV were designed to target mRNA (e.g., AUG region of different segments [ 36–40 ], conserved region [ 41 ], or structures [ 42 ] in NP, or UTRs [ 43 , 44 ]). For IAV vRNA, only the conserved 5′ and 3′ ends forming the panhandle structure have been targeted [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics studies showed the possibility of conserved structures both in (+) and in (–) RNA strands 6 , 7 . Only several of these motifs have been examined experimentally, and very few have been studied in vivo 2 , 8 10 . Only for two entire viral genomic segments, 8 and 7, has secondary structure been determined 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the conserved structures in segments 7 and 8 were shown to affect splicing14. Conserved structures were also suggested to fold in several domains of segment 51516.…”
mentioning
confidence: 96%